Development of hypobranchial muscles with special reference to the evolution of the vertebrate neck - Adachi, Noritaka (Zoological Lett, 2018)
BACKGROUND: The extant vertebrates include cyclostomes (lamprey and hagfish) and crown gnathostomes (jawed vertebrates), but there are various anatomical disparities between these two groups. Conspicuous in the gnathostomes is the neck, which occupies the interfacial domain between the head and trunk, including the occipital part of the cranium, the shoulder girdle, and the cucullaris and hypobranchial muscles (HBMs). Of these, HBMs originate from occipital somites to form the ventral pharyngeal and neck musculature in gnathostomes. Cyclostomes also have HBMs on the ventral pharynx, but lack the other neck elements, including the occipital region, the pectoral girdle, and cucullaris muscles. These anatomical differences raise questions about the evolution of the neck in vertebrates. RESULTS: In this study, we observed developing HBMs as a basis for comparison between the two groups and show that the arrangement of the head–trunk interface in gnathostomes is distinct from that of lampreys. Our comparative analyses reveal that, although HBM precursors initially pass through the lateral side of the pericardium in both groups, the relative positions of the pericardium withrespect to the pharyngeal arches differ between the two, resulting in diverse trajectories of HBMs in gnathostomes and lampreys. CONCLUSIONS: We suggest that a heterotopic rearrangement of early embryonic components, including the pericardium and pharyngeal arches, may have played a fundamental role in establishing the gnathostome HBMs, which would also have served as the basis for neck formation in the jawed vertebrate lineage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40851-018-0087-x) contains supplementary material, which is available to authorized users.